2009
DOI: 10.3945/ajcn.2009.27601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term high-protein compared with normal-protein diets on renal hemodynamics and associated variables in healthy young men

Abstract: A short-term HP diet alters renal hemodynamics and renal excretion of uric acid, sodium, and albumin. More attention should be paid to the potential adverse renal effects of HP diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
4
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 38 publications
4
47
4
6
Order By: Relevance
“…Also, our data reveal a J-shaped relationship between UA and the intake of all dietary components except fiber. Previous investigations regarding the association between dietary intake and UA showed increased serum UA levels with higher intake of sugar-sweetened beverages (24), calories (25), and protein (25,26), and lower intake of vitamin C (27). A study using NHANES data in adults revealed that a higher intake of fiber correlated with lower serum UA levels (28), which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 95%
“…Also, our data reveal a J-shaped relationship between UA and the intake of all dietary components except fiber. Previous investigations regarding the association between dietary intake and UA showed increased serum UA levels with higher intake of sugar-sweetened beverages (24), calories (25), and protein (25,26), and lower intake of vitamin C (27). A study using NHANES data in adults revealed that a higher intake of fiber correlated with lower serum UA levels (28), which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, as shown previously, HP diets cause elevation of glomerular filtration rate and hyperfiltration (Kim and Linkswiler, 1979;Schuette et al, 1980;Zemel et al, 1981;Brenner et al, 1982;Bilo et al, 1989;Metges and Barth, 2000;Tuttle et al, 2002;Frank et al, 2009;Burodom, 2010). In animal models, HP diets induce a renal hypertrophy (Addis, 1926;Wilson, 1933;Hammond and Janes, 1998) but not systematically (Robertson et al, 1986;Collins et al, 1990;Lacroix et al, 2004), and to our knowledge, the link between protein-induced renal hypertrophy or hyperfiltration and the initiation of renal disease in healthy individuals has not been clearly shown.…”
Section: Protein Intake Kidney Function and Kidney Stone Formationmentioning
confidence: 87%
“…In addition, accurate timing ensured a complete 24-hour urine collection, which took place during the 24-hour ambulatory monitoring under the supervision of healthcare personnel as reported previously (29). Another possible limitation is that we did not control for protein intake that is known to affect GFR (30). However, our data were obtained from a homogeneous cohort of people with † P=0.02 versus Hyp→Nor.…”
Section: Discussionmentioning
confidence: 99%